Analysis of genetic and phenotypic heterogeneity in juvenile polyposis. - Woodford-Richens, K; Bevan, S; Churchman, M; Dowling, B; Jones, D; Norbury, C; Hodgson, S; Desai, D; Neale, K; Phillips, R; Young, J; Leggett, B; et al. (2000)
BACKGROUND: Juvenile polyposis syndrome (JPS) is characterised by gastrointestinal (GI) hamartomatous polyposis and an increased risk of GI malignancy. Juvenile polyps also occur in the Cowden (CS), Bannayan-Ruvalcaba-Riley (BRRS) and Gorlin (GS) syndromes. Diagnosing JPS can be problematic because it relies on exclusion of CS, BRRS, and GS. Germline mutations in the PTCH, PTEN and DPC4 (SMAD4) genes can cause GS, CS/BRRS, and JPS, respectively. AIMS: To examine the contribution of mutations in PTCH, PTEN, and DPC4 (SMAD4) to JPS. METHODS: Forty seven individuals from 15 families and nine apparently sporadic cases with JPS were screened for germline mutations in DPC4, PTEN, and PTCH. RESULTS: No patient had a mutation in PTEN or PTCH. Five different germline mutations were detected in DPC4; three of these were deletions, one a single base substitution creating a stop codon, and one a missense change. None of these patients had distinguishing clinical features. CONCLUSIONS: Mutations in PTEN and PTCH are unlikely to cause juvenile polyposis in the absence of clinical features indicative of CS, BRRS, or GS. A proportion of JPS patients harbour DPC4 mutations (21% in this study) but there remains uncharacterized genetic heterogeneity in JPS.